HIV-associated neurocognitive disorder: key implications of the microbiota-gut-brain axis - Hu, Aizhen; Zaongo, Silvere D.; Harypursat, Vijay; Wang, Xin; Ouyang, Jing; Chen, Yaokai (Frontiers in Microbiology, 2024)
HIV-associated neurocognitive disorder (HAND) is now recognized to be relatively common in people living with HIV (PLWH), and remains a common cause of cognitive impairment. Unfortunately, the fundamental pathogenic processes underlying this specific outcome of HIV infection have not as yet been fully elucidated.With increased interest in research related to the microbiota-gut-brain axis, the gutbrain axis has been shown to play critical roles in regulating central nervous system disorders such as Alzheimer's disease and Parkinson's disease. PLWH are characterized by a particular affliction, referred to as gut-associated dysbiosis syndrome, which provokes an alteration in microbial composition and diversity, and of their associated metabolite composition within the gut. Interestingly, the gut microbiota has also been recognized as a key element which both positively and negatively influences human brain health, including the functioning and development of the central nervous system (CNS). In this review, based on published evidence, we critically discuss the relevant interactions between the microbiota-gut-brain axis and the pathogenesis of HAND in the context of HIV infection. It is likely that HAND manifestation in PLWH mainly results from (i) gut-associated dysbiosis syndrome and a leaky gut on the one hand and (ii) inflammation on the other hand. In other words, the preceding features of HIV infection negatively alter the composition of the gut microbiota (microbes and their associated metabolites) and promote proinflammatory immune responses which singularly or in tandem damage neurons and/or induce inadequate neuronal signaling. Thus, HAND is fairly prevalent in PLWH. This work aims to demonstrate that in the quest to prevent and possibly treat HAND, the gut microbiota may ultimately represent a therapeutically targetable 'host factor'.